What do changing weather and climate shocks and stresses mean for the UK food system? - Falloon, P; Bebber, DP; Dalin, C; Ingram, J; Mitchell, DM; Hartley, T; Johnes, P; Newbold, T; Challinor, A; Finch, J; Galdos, M; Petty, C; et al. (IOP Publishing, 2022)
We identify major knowledge gaps in the primary impacts of extreme weather and climate change across the UK's food system, its functioning and their interactions to provide information to support adaptation and resilience planning. Future shocks and stresses due to changes in weather and climate extremes will have significant impacts on the UK food system. Key knowledge gaps remain in our understanding of their impacts on non-cereal crops, livestock and fisheries production, on the food chain beyond primary production, on the longer-term impacts, and in an integrated, full system view of impacts that accounts for cumulative impacts, interactions, feedbacks and the interplay between domestic and overseas elements of the UK food system. These knowledge gaps need to be urgently addressed to ensure future climate resilience of the UK food system. There are several areas where research could better support decision-making towards increased resilience to weather and climate shocks in both food policy and business sectors. We note the need for a step change in the collection, quality, synthesis and application of a broad range of weather and food chain data and information across time and space. There is a need to develop tools to support the inclusion of the "missing middle" of food chain and policy discussions that incorporate weather and climate impacts: processing/packaging, transport, storage, wholesale, retail and disposing/reusing. Greater integration of climate, biophysical, social, political and economic research is required to characterise geo-political influences on food system climate resilience. Further work is needed to assess adaptation actions needed in response, and their knock-on trade-offs and consequences across sectors, and their interactions. The challenges identified here suggest the need for challenge-led, connective, interdisciplinary approaches to future funding initiatives in support of achieving food system resilience to weather and climate shocks.